2023
DOI: 10.1111/gcb.17080
|View full text |Cite
|
Sign up to set email alerts
|

Distinct, direct and climate‐mediated environmental controls on global particulate and mineral‐associated organic carbon storage

Paige M. Hansen,
Rebecca Even,
Alison E. King
et al.

Abstract: Identifying controls on soil organic carbon (SOC) storage, and where SOC is most vulnerable to loss, are essential to managing soils for both climate change mitigation and global food security. However, we currently lack a comprehensive understanding of the global drivers of SOC storage, especially with regards to particulate (POC) and mineral‐associated organic carbon (MAOC). To better understand hierarchical controls on POC and MAOC, we applied path analyses to SOC fractions, climate (i.e., mean annual tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 180 publications
(143 reference statements)
0
1
0
Order By: Relevance
“…Overall, our study confirms results from recent studies conducted at regional and global scales showing that physical fractions have different drivers (King et al, 2023 ;Hansen et al, 2024) and strongly supports the idea that it is relevant and informative to consider SOC fractions (either physical or thermal) instead of TOC alone. However, it is difficult to compare our results directly with those of these recent studies.…”
Section: Soc Fractions With Different Quantities Drivers and Biogeoch...supporting
confidence: 90%
See 3 more Smart Citations
“…Overall, our study confirms results from recent studies conducted at regional and global scales showing that physical fractions have different drivers (King et al, 2023 ;Hansen et al, 2024) and strongly supports the idea that it is relevant and informative to consider SOC fractions (either physical or thermal) instead of TOC alone. However, it is difficult to compare our results directly with those of these recent studies.…”
Section: Soc Fractions With Different Quantities Drivers and Biogeoch...supporting
confidence: 90%
“…The higher proportion of POC in forest than in grassland and cropland soils (0.13, 0.17, and 0.27 in croplands, grasslands, and forests, respectively) was also observed in Lugato et al (2021) who used results from 352 physical fractionations obtained using a fractionation protocol similar to ours on samples from the LUCAS soil monitoring network. It was also observed by Hansen et al (2024) on a global dataset combining physical fractions obtained with different protocols. Other studies showed similar results for POC, but comparisons are less straightforward as the physical fractionation protocols used are significantly different from those used in our study.…”
Section: Drivers Of the Different Soc Fractions Quantitiesmentioning
confidence: 79%
See 2 more Smart Citations
“…However, controls on the formation and accrual of MAOC are only partially resolved currently. It is not entirely clear what environmental variables (processes) predominate the accumulation patterns and capacity of MAOC in soils (Begill et al, 2023;Cotrufo et al, 2019;Hansen et al, 2024). Answering this question will contribute to our understanding of the mechanisms underlying MAOC formation and potentially provoke management strategies to enhance MAOC sequestration for climate change mitigation.…”
Section: Introductionmentioning
confidence: 99%